The Urgency of Certification Compensation in Enhancing Teacher Performance: A Case Study of Smp Negeri 9 Muaro Jambi - Maisah (International Journal of Educational and Life Sciences, 2024)
This study explores the urgency of certification compensation in enhancing teacher performance, focusing on SMP Negeri 9 Muaro Jambi. The research aims to contribute to the understanding of how financial incentives tied to teacher certification impact professional performance. Using a qualitative case study approach, data were collected through interviews, observations, and document analysis involving certified teachers as participants. Data were gathered over a two-month observation period. The findings reveal that certification compensation significantly motivates teachers, leading to increased dedication, improved teaching quality, and better alignment with educational goals. However, challenges such as administrative delays were noted. This study highlights the need for efficient implementation of certification compensation policies to optimize teacher performance, providing practical implications for educational management.